Gender-related differences and its effects on ureteroscopy success - S. V. Kotov; A. A. Nemenov; R. A. Perov; N. M. Sokolov (Вестник урологии, 2023)
Introduction. The prevalence of urinary stone disease (USD) historically considered a predominantly male disease. It has been rising over the last several decades with the rate of increase being higher among females. However, factors such as stone localisation, size, and density are usually analysed in postureteroscopic complications, and reports on gender-specific differences in the treatment of USD are scarce.Objective. To investigate the impact of gender differences on treatment success, intraoperative and postoperative complications in patients undergoing ureteroscopy.Materials & methods. A total of 300 patients with USD, who were performed ureteroscopic interventions in the period from September 2021 to November 2022 in Yudin City Clinical Hospital. Depending on gender, patients were divided into two groups — 194 (64.7%) men and 106 (35.3%) women. Recurrent USD was observed in 71 (36.6%) cases in Group I and in 45 (42.5%) cases in Group II, with an average recurrence time of 4.3 and 6.3 years, respectively. Male and female patients have had stone location in the upper third in 14.4% and 18.9% of cases, in the middle third in 18% and 6.6% (p = 0.005), in the lower third in 36 .1% and 49.1% (p = 0.04), in the intramural ureter in 28.9% and 21.7%, and in several localisations in 2.6% and 3.8% of cases, respectively.Results. The duration of surgery did not differ in both groups and composed 41.6 minutes. Internal ureteral stent placement was in 37 (19.1%) male patients and in 14 (13.2%) female patients. Based on specialised postureteroscopic lesion scales such as PULS and Satava, the percentage of complications in Groups I and II was 2.1 and 2.8 and 4.1 and 9.4 (p = 0.03) respectively.Conclusion. The development of acute renal colic in women with patients less intensity than in the male group leads to hospitalisation in the delayed period. In female patients, the number of postureteroscopic complications has higher rates due to the size and density of the stone and its location.